Portable Paper‐Based Nucleic Acid Enrichment for Field Testing. Issue 11 (16th February 2023) - Mei, Junyang; Wang, Dandan; Zhang, Yiheng; Wu, Dan; Cui, Jinhui; Gan, Mingzhe; Liu, Peifeng
Abstract: Point‐of‐care testing (POCT) can be the method of choice for detecting infectious pathogens; these pathogens are responsible for not only infectious diseases such as COVID‐19, but also for certain types of cancers. For example, infections by human papillomavirus (HPV) or Helicobacter pylori (H. pylori) are the main cause of cervical and stomach cancers, respectively. COVID‐19 and many cancers are treatable with early diagnoses using POCT. A variety of nucleic acid testing have been developed for use in resource‐limited environments. However, questions like unintegrated nucleic acid extraction, open detection systems increase the risk of cross‐contamination, and dependence on expensive equipment and alternating current (AC) power supply, significantly limit the application of POCT, especially for on‐site testing. In this paper, a simple portable platform is reported capable of rapid sample‐to‐answer testing within 30 min based on recombinase polymerase amplification (RPA) at a lower temperature, to detect SARS‐CoV‐2 virus and H. pylori bacteria with a limit of detection as low as 4 × 10 2 copies mL −1 . The platform used a battery‐powered portable reader for on‐chip one‐pot amplification and fluorescence detection, and can test for multiple (up to four) infectious pathogens simultaneously. This platform can provide an alternative method for fast and reliable on‐site diagnostic testing. Abstract : A simple portable platform is reported for rapid nucleic acid field testing of SARS‐CoV‐2 and H. pylori with minimum instruments. Including paper‐based sample processing, isothermal amplification and readout modules, it realizes the sample‐to‐answer detection within 30 min and output visual results, with the detection limit of 400 copies mL −1 . The platform is flexible and can detect multiple pathogens in one single test.